2010
DOI: 10.1016/j.jse.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of type II superior labrum, anterior to posterior (SLAP) repair: Prospective evaluation at a minimum two-year follow-up

Abstract: Hypothesis Patients with type II superior labrum, anterior to posterior (SLAP) lesions will have improved function and decrease pain at a minimum two years after arthroscopic SLAP repair using bioabsorbable suture anchor fixation. Materials and Methods The study population consisted of 48 patients who underwent arthroscopic SLAP repair. Subjective shoulder scores, range of motion, and strength (post-operative only) were assessed pre-operatively and at a minimum of two years post-operatively. Results At an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 19 publications
3
100
0
Order By: Relevance
“…1.0); however, the other group had a greater chance of successful return to full activity (OR ¼ 3.5; 95% CI ¼ 0.8, 16.3) than did baseball athletes. The 2 investigations also showed that overhead athletes (odds ¼ 1.3-2.5) and nonoverhead/other athletes (odds ¼ 2.0-5.0) both had positive odds for returning to full activity after superior labral repair with soft tissue debridement, but again the ORs favored the nonoverhead (OR ¼ 1.5; 95% CI ¼ 0.4, 6.0) 19 and other (OR ¼ 2.0; 95% CI ¼ 0.2, 19.9) groups. 18 These observations were not different, as each 95% CI contained the value 1.0.…”
Section: Return To Preinjury Levels Of Participationmentioning
confidence: 95%
See 4 more Smart Citations
“…1.0); however, the other group had a greater chance of successful return to full activity (OR ¼ 3.5; 95% CI ¼ 0.8, 16.3) than did baseball athletes. The 2 investigations also showed that overhead athletes (odds ¼ 1.3-2.5) and nonoverhead/other athletes (odds ¼ 2.0-5.0) both had positive odds for returning to full activity after superior labral repair with soft tissue debridement, but again the ORs favored the nonoverhead (OR ¼ 1.5; 95% CI ¼ 0.4, 6.0) 19 and other (OR ¼ 2.0; 95% CI ¼ 0.2, 19.9) groups. 18 These observations were not different, as each 95% CI contained the value 1.0.…”
Section: Return To Preinjury Levels Of Participationmentioning
confidence: 95%
“…Researchers [16][17][18][19][20][21] examining various types of overhead athletes after superior labral repair with concurrent procedures reported return to preinjury levels of participation ranging from 41% to 86%. Concurrent procedures consisted of debridement of partial-thickness rotator cuff tear or the labrum, subacromial decompression, bursectomy, or distal clavicle excision.…”
Section: Return To Preinjury Levels Of Participationmentioning
confidence: 99%
See 3 more Smart Citations